2009
DOI: 10.1371/journal.pone.0007892
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling during Early Acute Febrile Stage of Dengue Infection Can Predict the Disease Outcome

Abstract: BackgroundWe report the detailed development of biomarkers to predict the clinical outcome under dengue infection. Transcriptional signatures from purified peripheral blood mononuclear cells were derived from whole-genome gene-expression microarray data, validated by quantitative PCR and tested in independent samples.Methodology/Principal FindingsThe study was performed on patients of a well-characterized dengue cohort from Recife, Brazil. The samples analyzed were collected prospectively from acute febrile de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
69
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(75 citation statements)
references
References 48 publications
5
69
0
1
Order By: Relevance
“…The timing of sample collection is clearly a major factor in the transcriptional signature, with samples collected during the febrile phase having characteristic antiviral profiles, e.g., with interferon-stimulated genes being highly prominent (11,26,36), while those collected during the afebrile stage having predominantly metabolic profiled (26,36). Studies of peripheral blood mononuclear cells (PBMC) (i.e., minus the neutrophil population) have also been described (30,40). In short, however, all previous microarray studies of the dengue host response have used relatively small amounts of samples collected at heterogenous time points and rarely included patients with DSS, the commonest life-threatening complication in children.…”
Section: Discussionmentioning
confidence: 99%
“…The timing of sample collection is clearly a major factor in the transcriptional signature, with samples collected during the febrile phase having characteristic antiviral profiles, e.g., with interferon-stimulated genes being highly prominent (11,26,36), while those collected during the afebrile stage having predominantly metabolic profiled (26,36). Studies of peripheral blood mononuclear cells (PBMC) (i.e., minus the neutrophil population) have also been described (30,40). In short, however, all previous microarray studies of the dengue host response have used relatively small amounts of samples collected at heterogenous time points and rarely included patients with DSS, the commonest life-threatening complication in children.…”
Section: Discussionmentioning
confidence: 99%
“…Genomics (8,9) and proteomics (10)(11)(12) have been used by different research groups in an attempt to identify early markers of dengue disease and/or its severity. More recently, metabolomics, the study of low-molecular-weight metabolites of physiological relevance, has proved an important tool for studying the changes in host metabolism during the course of viral infections (13)(14)(15)(16)(17).…”
mentioning
confidence: 99%
“…However, a robust test incorporating a large panel of molecules will likely be required for the accurate prognosis and differential diagnosis of CM. Interestingly, a recent study conducted on a dengue cohort in Brazil demonstrated that microarray analysis of peripheral blood mononuclear cells could be used to design gene expression signatures that accurately predict which cases of acute febrile dengue progress into dengue hemorrhagic fever (28).…”
mentioning
confidence: 99%